The Role of Museums in Dealing with the Legacy of Conflict in Northern Ireland - Karine Bigand (Review of Irish Studies in Europe)
This article deals with the roles given to and taken by museums in addressing the legacy of conflict and contributing to reconciliation in Northern Irish society. It analyses the reasons for, relevance and feasibility of the role given to museums in good relations policies as well as the direction defined and changes entailed by the 2011 Museums Policy for Northern Ireland. Using several examples throughout Northern Ireland, it assesses to what extent the official recommendations have been integrated in museums’ mission statements, outreach services, exhibitions programmes and educational provisions, thereby outlining good practices and limitations found in the sector.